Un usage dévoyé de la « mainlevée » en protection de l’enfance ? - Claire Autant-Dorier (Sociétés et Jeunesses en Difficulté)
Our research examined an NGO which applies educational measures in open environment. Inspired by non take-up benefit of social benefits theories, it aims at studying how the translation process of users’ demands operates at local level of social policies.This article presents an issue considered as problematic by professionals : release decision taken in situations where they “don’t know what to do anymore”. Release is expected to be sentenced when there is no more need of protection or no more requests for assistance. Here it would rather mean the renunciation of assistance. And the acknowledgement of powerlessness allows the no commitment of resources. Theses situations reveal the tensions between the imperative to do with the family, the concern for protection of children, and the difficulty in mobilizing the right means at the right time. A specific case is considered : the paper describes how the educational stakeholders (dis)qualify the parents, leading to point out both their inability to act and their responsibility in the failure of situation.However the timeline reconstruction of the social support record shows some acceleration moments and some caesura during the measures. It makes appear that each actor is successively able or unable to act depending on the framing of the situation. Therefore, responsibility and ability to act seems to be distributed between all the stakeholders, human and non-human (reports, order of the judge, working hours, knives, institutions, partners, territory), which should be better recognized. Firstly, from a care perspective, more open negotiations should be maintained. Secondly, community work should really be developed.